The Wiley handbook of educational supervision - Zepeda, Sally J., 1956-; Ponticell, Judith A. (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
'The Handbook of Educational Supervision offers a view of the field of supervision as it has evolved to the present. Through this spotlight, we hope that the Handbook points the reader to the research, theory, and applications about supervision that have surfaced in the broader fields of educational leadership and teacher preparation to keep pace with what occurs in practice in preK-12 schools. This handbook is important because much of what we know about supervision rests between its theory and its applications in schools and systems that have provided fertile ground for supervision as we know it today'--
A policy and political history of educational supervision -- Foundations in adult development and learning: implications for educational supervision -- Theories of professions and the status of teaching -- Job-embedded learning: how school leaders can use job-embedded learning as a mechanism for school improvement -- Instructional supervision in the era of high-stakes accountability -- Accountability, control, and teachers' work in American schools -- Coming to understand the wicked problem of teacher evaluation -- Discretion and trust in professional supervisory practices -- Managing collaborative inquiry for continuously better practice: a cross-industry perspective -- Observation, feedback, and reflection -- Teacher mentoring in service of beginning teachers' learning to teach: critical review of conceptual and empirical literature -- Peer coaching in education: from partners to faculties and districts -- From supervision to'super vision:' a developmental approach to collaboration and capacity building -- Encouraging reflective practice in educational supervision through action research and appreciative inquiry -- National policy/standards: changes in instructional supervision since the implementation of recent federal legislation -- Teacher performance assessments mandated during the Duncan era -- Principal supervisors and the challenge of principal support and development -- The principal: building the future based on the past -- Necessity is the mother of re-invention: making teaching excellence the norm through policy and established clinical practice -- Improving teacher practice based knowledge: what teachers need to know and how they come to know it -- Shaping the school-wide learning environment through supervisory leadership -- High performing teachers, student achievement, and equity as an outcome of educational supervision -- Supervisory identity: cultural shift, critical pedagogy, and the crisis of supervision -- Conflicts, convergence, and wicked problems: the evolution of educational supervision.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 26, 2018).
Keywords: School supervision -- United States -- Handbooks, manuals, etc; Educational leadership -- United States -- Handbooks, manuals, etc; EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions; Educational leadership; School supervision; United States; Electronic books; Handbooks and manuals; Handbooks and manuals